A collaborative process for developing a weight management toolkit for general practitioners in Australia—an intervention development study using the Knowledge To Action framework. Issue 1 (December 2016) - Sturgiss, Elizabeth; Douglas, Kirsty
Abstract Background Obesity is commonly seen in the Australian general practice population; however, few resources are specifically targeted at GPs working with these patients. The National Health and Medical Research Council (Australia) guideline for managing patients who are overweight and obese supports the involvement of a regular health professional. As 85 % of the population visit a GP annually, resources to support GPs working with this patient population are needed. This study describes the collaborative process used to develop an obesity management programme based on current Australian guidelines for GPs and their patients to be used in primary care. The Knowledge To Action framework was applied to develop a weight management toolkit for GPs based on current Australian guidelines. This draft was then reviewed by clinical GPs, GP registrars, consumer representatives and allied health professionals using focus groups and interviews. The participants gave feedback on the content, layout and acceptability of the documents. The feedback from the stakeholder groups was evaluated, and changes were incorporated into the final documents. A graphic designer was contracted to assist with the layout to improve useability and attractiveness of the documents. Results A total of 38 participants gave feedback on the draft weight management programme, and the research team amalgamated their responses to further improve the documents. The general response from GPs and consumer representatives was positive with most conveying their wish to try the programme themselves. Conclusions "The Change Program" is a practical tool for Australian GPs to use with their patients who are overweight or obese. It was developed in collaboration with GPs, allied health professionals and consumer stakeholders based on current Australian guidelines. It is currently being piloted in five general practices.